A decreased peritumoral CD1a+ cell number predicts a worse prognosis in oral squamous cell carcinoma. Issue 6 (6th February 2018) - Jardim, Juscelino F; Gondak, Rogério; Galvis, Marisol M; Pinto, Clovis A L; Kowalski, Luiz P
Abstract : Aims: Dendritic cells (DCs) are known to play a central role in the regulation of both innate and adaptive immunological responses, including antitumour immunity. The aim of this study was to evaluate the prognostic impact of intratumoral and peritumoral DCs in oral squamous cell carcinoma (OSCC) affecting the tongue and floor of the mouth. Methods and results: Immunohistochemistry for CD1a and CD83 was performed in 53 patients with OSCC in the tongue and floor of the mouth. The markers were evaluated by automated examination in intratumoral and peritumoral compartments, and the results were expressed as density of cells/mm 2 . Correlations between these data and clinicopathological and survival outcomes were investigated. Depletion of peritumoral CD1a+ cells was associated with lymph node metastasis ( P = 0.05), whereas depletion of peritumoral CD83+ cells was correlated with smoking history ( P = 0.04), lymph node metastasis ( P = 0.015), and extracapsular spread of lymph nodes ( P = 0.018). Peritumoral CD1a+ was correlated with recurrence ( P = 0.007) and overall survival ( P = 0.03). The results of the survival analysis with the Cox proportional hazard model showed that depletion of peritumoral CD1a+ cells is an independent factor associated with overall survival and disease‐free survival. Conclusion: Our results suggest that depletion of peritumoral CD1a+ cells is a strong independent prognostic factor, predicting a higher recurrence rates and worse survival outcomes.